Acylation – A New Means to Control Traffic Through the Golgi - Ernst, Andreas M.; Toomre, Derek; Bogan, Jonathan S. (Frontiers in Cell and Developmental Biology, 2019)
The Golgi is well known to act as center for modification and sorting of proteins for secretion and delivery to other organelles. A key sorting step occurs at the trans-Golgi network and is mediated by protein adapters. However, recent data indicate that sorting also occurs much earlier, at the cis-Golgi, and uses lipid acylation as a novel means to regulate anterograde flux. Here, we examine an emerging role of S-palmitoylation/acylation as a mechanism to regulate anterograde routing. We discuss the critical Golgi-localized DHHC S-palmitoyltransferase enzymes that orchestrate this lipid modification, as well as their diverse protein clients (e.g. MAP6, SNAP25, CSP, LAT, -adrenergic receptors, GABA receptors, GLUT4 glucose transporters). Critically, for integral membrane proteins, S-acylation can act as new a “self-sorting” signal to concentrate these cargoes in rims of Golgi cisternae, and to promote their rapid traffic through the Golgi or, potentially, to bypass the Golgi. We discuss this mechanism and examine its potential relevance to human physiology and disease, including diabetes and neurodegenerative diseases.